Ethno-Flipped Learning of Mathematics Lessons Based on Internalizing Data from Tri Mandala Concept on Schoology Platform - Ardana, I Made; Sugiarta, I Made; Sudatha, I Gde Wawan; Andayani, Made Susi Lissia; Divayana, Dewa Gede Hendra (Journal of Applied Data Sciences, 2024)
In the digital era like today, maximum Mathematics learning outcomes in the affective and psychomotor domains are difficult to obtain through full online learning. This difficulty is influenced by environmental and cultural factors inherent in students’ lives. Therefore, an idea in the form of innovative learning model is needed to internalize cultural values and local wisdom in online learning. Based on the problems and needs of their solutions, the innovative model that emerged in this study is called Ethno-Flipped learning of Mathematics lessons based on internalizing data from Tri Mandala concept on the Schoology platform. The aim of this research is to demonstrate an Ethno-Flipped Learning design based on internalizing data from the Tri Mandala concept on the Schoology platform. This research approach is development with a focus on development at several stages, including: research and field data collection, planning, design development, initial trials, and revision of initial trial results. The number of personnel involved in the initial trial was 104 respondents. The data collection tool for the initial trial results was a questionnaire consisting of 10 questions related to the model design. The analysis was carried out by comparing the percentage of model design quality with the five scale categorization standards. The findings or research results show that the Ethno-Flipped learning design especially for Mathematics lessons based on internalizing data from the Tri Mandala concept on the Schoology platform is classified as good quality by a quality percentage of 87.54%. The contribution of this research is that it provides new knowledge about an innovative learning model based on Balinese culture and local wisdom combined with an online learning platform. The novelty of this research is in the form of an innovative learning model design that combines the Flipped Classroom learning model, the Ethno-Mathematics approach, and the Tri Mandala concept.